Synchronous Renal Malignancy Presenting as Recurrent Urinary Tract Infections. (26th July 2010) - Dutta, G.; Silver, D.; Oliff, A.; Harrison, A.
Abstract : Renal cell carcinoma (RCC) and urothelial carcinoma of the upper urinary tract are not uncommon urological malignancies. Their simultaneous occurrence in a patient is, however, extraordinarily rare. We report the case of a patient who underwent unilateral nephrectomy for suspected RCC and diagnosed transitional cell carcinoma of the superior pelvis. Preoperative imaging was suspicious for renal pelvic involvement, which was confirmed upon performing cystoscopy and biopsy of the suspected lesion preoperatively. This preoperative approach was especially appropriate as a nephron saving procedure was being considered prior to the discovery of the synchronous lesion. We discuss this rare simultaneous occurrence of synchronous malignancies in the same kidney.